2004
DOI: 10.1373/clinchem.2003.024877
|View full text |Cite
|
Sign up to set email alerts
|

Quality Assessment of Interpretative Commenting in Clinical Chemistry

Abstract: A case summary/rationale was also returned to participants. Results: There was considerable diversity in the range of interpretative comments received for each case report. Although the majority of comments received were felt to be acceptable by the expert panel, some comments were felt to be inappropriate, misleading, or in a few instances, dangerous. Conclusion: The golden rule in medicine is "do no harm". Although there is no objective evidence that interpretive comments help to improve patient out-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 11 publications
4
28
0
1
Order By: Relevance
“…It is alarming that although in the present study laboratory professionals responsible for coagulation were asked to interpret the mixing studies, only staff at 49% of the laboratories in which mixing studies were implemented could adequately discriminate between inhibitory and non-inhibitory forms of uAPTT in all three scenarios. These results are similar to those of the postanalytical Quality Assurance Program in Australia, wherein participants were asked to add interpretative comments to a set of non-esoteric laboratory test results, and in which ≥ 50% of the interpretations were inappropriate and/or misleading [25].…”
Section: Interpretations Of Uaptt In Mixing Study Scenariossupporting
confidence: 59%
See 1 more Smart Citation
“…It is alarming that although in the present study laboratory professionals responsible for coagulation were asked to interpret the mixing studies, only staff at 49% of the laboratories in which mixing studies were implemented could adequately discriminate between inhibitory and non-inhibitory forms of uAPTT in all three scenarios. These results are similar to those of the postanalytical Quality Assurance Program in Australia, wherein participants were asked to add interpretative comments to a set of non-esoteric laboratory test results, and in which ≥ 50% of the interpretations were inappropriate and/or misleading [25].…”
Section: Interpretations Of Uaptt In Mixing Study Scenariossupporting
confidence: 59%
“…It is generally advisable that only professionals with clear expertise in the particular laboratory field should be charged with interpreting laboratory results [25,26]. It is alarming that although in the present study laboratory professionals responsible for coagulation were asked to interpret the mixing studies, only staff at 49% of the laboratories in which mixing studies were implemented could adequately discriminate between inhibitory and non-inhibitory forms of uAPTT in all three scenarios.…”
Section: Interpretations Of Uaptt In Mixing Study Scenariosmentioning
confidence: 76%
“…This is not surprising given that doctors at graduation often lack adequate training in test ordering and result interpretation (4). However, inappropriate commenting by inadequately trained laboratory personnel can be dangerous (5,6). Training in pathology consultation has to be undertaken in a formal manner for this activity to be performed effectively (7).…”
Section: Introductionmentioning
confidence: 99%
“…Training in pathology consultation has to be undertaken in a formal manner for this activity to be performed effectively (7). There is now some acceptance in the clinical chemistry profession for the need and ability to assess the quality of interpretative services offered by the clinical chemistry laboratory (6,8,9). We describe a study of interpretative commenting ability among laboratory personnel in the Asia-Pacific region and Africa.…”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that they lead to improved outcomes compared to reports without comments [13]. The quality of interpretive commenting in clinical chemistry has been assessed by proficiency testing schemes and has found that unacceptable interpretation can be made [14][15][16][17] and lead to the conclusion that formal training of pathologists and clinical scientists should be provided [18][19][20], concentrating on how to comment as much as what to comment [21,22].…”
Section: The Post-analytical Phasementioning
confidence: 99%